2011
DOI: 10.1002/j.2333-8504.2011.tb02244.x
|View full text |Cite
|
Sign up to set email alerts
|

PERFORMANCE AND PASSING RATE DIFFERENCES OF AFRICAN AMERICAN AND WHITE PROSPECTIVE TEACHERS ON PRAXISTM EXAMINATIONS: A JOINT PROJECT OF THE NATIONAL EDUCATION ASSOCIATION (NEA) AND EDUCATIONAL TESTING SERVICE (ETS)

Abstract: This report focuses on two aspects of teacher supply and quality: (a) the under‐representation of racial/ethnic minorities, especially African Americans in the teaching pool, and (b) teacher candidates' performance on licensure assessments, including general skills tests in reading, writing, and mathematics (known as Praxis I®) and selected tests covering areas of content and pedagogy (known as Praxis II®). The report presents trends in the overall and minority teaching workforce, utilizes some of the availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 6 publications
3
44
3
Order By: Relevance
“…The data presented in Nettles et al () showed that relative to Camara and Schmidt (), the Praxis I Reading score gap between African American and White candidates was larger than that for the SAT and more like that for the GMAT. The gap in Praxis I Writing was more comparable to that for the SAT, and the gap in Praxis I Mathematics was larger than that for the GRE Quantitative section.…”
Section: Literature Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…The data presented in Nettles et al () showed that relative to Camara and Schmidt (), the Praxis I Reading score gap between African American and White candidates was larger than that for the SAT and more like that for the GMAT. The gap in Praxis I Writing was more comparable to that for the SAT, and the gap in Praxis I Mathematics was larger than that for the GRE Quantitative section.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Tyler et al () showed that performance and passing rate gaps were largest with respect to performance comparisons of White test takers with those from other minority race/ethnicity populations, a finding consistent with research previously conducted by Camara and Schmidt () concerning performance gaps on other standardized admissions tests. Nettles, Scatton, Steinberg, and Tyler () conducted a comprehensive analysis of performance differences between African American and White prospective teachers on the PB version of Praxis I tests. The study made use of extensive information collected about test takers at the time of registration .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Those problems related to graduate education (Wendler et al 2010), minority representation in teaching (Nettles et al 2011), developing and implementing teacher evaluation systems (Goe et al 2011), testing at the pre-K level (Ackerman and Coley 2012), achievement gaps in elementary and secondary education (Barton and Coley 2010), and parents opting their children out of state assessment (Bennett 2016).…”
Section: Education Policy Analysismentioning
confidence: 99%
“…A recent study by ETS researchers found that minorities remain underrepresented in the teaching profession and pool of prospective teachers (Nettles et al 2011). The authors analyzed the performance of minority test takers who took ETS's PRAXIS ® teacher-certification examinations for the first time between 2005 and 2009 and the relationship of performance with test takers' demographic, socioeconomic, and educational backgrounds, including undergraduate major and undergraduate grade point average (UGPA).…”
Section: Research On the Teacher Education Pipelinementioning
confidence: 99%